STRATEGI SILVIKULTUR INTENSIF UNTUK PEMBANGUNAN HQTAN TANAMAN:PENGALAMAN DARI HUTAN TANAMAN Acacia mangium DI PT MUSl HUTAN PERSADA (Intemsive Silvicultural Strategy for the Development of Plantation Forests : Experience from the Acacia mangium Plantation - , Hardjono Arisman ([Yogyakarta] : Fak. Kehutanan UGM, 2000)
The paper describes the strategy of intensive silviculture for plantation forest development with a particular reference to the experience of Acacia mangium plantation development at PT.Musi Hutan Persada in South Sumatra. The feasibility study on the land suitability for plantation development is elucidated. Species trial and provenance test to select the best species and provenances are extremely essential. It is also ofpararnount importance to use genetically improved planting materials for establishing plantation forests. The use of conventional breeding program seems adequate to obtain improved planting materials and more sophisticated techniques are only used as complementary one. Sound silvicultural practices such as land preparation, planting, spacing, fertilizing and tending are mandatory to obtain productive plantation forests. It is mentioned that inter-rotation site management is very vital to sustain plantation productivity